Water quality for uses of human consumption and protection of the aquatic life in the Los Laureles reservoir of Tegucigalpa (2002-2016) - Rodríguez Cruz, German Onil (2022)
[Introduction]: From the Los Laureles reservoir it is generated an enormous amount of water quality data that are often not analysed and interpreted in a comprehensive manner, a limitation that also occurs in others reservoirs in the country and over the Central American region. This situation limits the knowledge for taking preventive actions in the face of contamination scenarios when the parameters are observed or analysed separately. [Objective]: The purpose of the research was to calculate and use different water quality indices in the Los Laureles reservoir during the time 2002-2016 with historical data, and analyse possible natural or anthropic factors that have contributed to its deterioration. [Methodology]: The indices were calculated using WQI software (version 1.2), based on historical information generated by the SANAA Laboratory at three sampling points (curtain, centre and tail), and including up to 23 physicochemical, microbiological, metals and metalloids parameters. Three different guidelines were used: one guideline of water quality for human consumption use and two guidelines for water life protection use. [Results]: The quality indices categorized the water quality of the Los Laureles reservoir for the use of human consumption as marginal to poor. The categorisation of use for aquatic life protection was regular. The decrease in the values of the indices and the categorization of water quality was observed when more parameters and samplings were included. [Conclusion]: In the comprehensive study, a historical decrease in quality was recorded due to the increase in the values of the parameters that exceeded the guidelines up to more than 25 times, even when it is only a parameter that will contribute to its decrease. In other words, the number of times that a parameter exceeded the guidelines had more influence than the number of failed parameters.